Cyber Warfare: Exploring New Dimensions in the History of Modern Warfare in Indonesia - Lusiana Dwiyanti; Ayu Agung; Joni Widjayanto; Robby MT (Faculty of Law, Universitas Pekalongan, 2025)
Cyber warfare has become a significant threat in the current digital era, with an increasing number of cyberattacks targeting critical infrastructure and national defence systems. As cyberattacks continue to evolve and impact various sectors, this study aims to explore a new dimension of modern warfare that has not been extensively documented in Indonesia's official war history. The primary focus of this study is to document and analyse cyber conflicts as a form of new warfare history, which is becoming increasingly relevant in the digital world. A comparison between physical warfare and cyber warfare is conducted to examine the differences in impact, actors, and strategies employed in both forms of conflict. In addition, the study also examines the weaknesses in Indonesia’s cyber defence structure over the past decade and provides recommendations for developing a stronger and more adaptive cyber defence doctrine. Through a historiographical approach and critical analysis, this study is expected to contribute to the development of Indonesia’s digital defence foundations and the formulation of a more adaptive cyber defence doctrine to enhance Indonesia's preparedness in facing future cyber threats.